Influence of the Attachment of a Gold(I) Phosphine Moiety at the Upper Rim of a Calix[4]pyrrole on the Binding of Tetraalkylammonium Chloride Salts. Issue 15 (19th February 2020) - Sun, Qingqing; Aragay, Gemma; Pinto, Andrea; Aguiló, Elisabet; Rodríguez, Laura; Ballester, Pablo
Abstract: We report the synthesis of an unprecedented mono‐gold(I) phosphine complex based on a "two‐wall" aryl‐ethynyl extended calix[4]pyrrole. We describe and compare the binding properties of the parent 10α, 20α‐bis‐aryl‐ethynyl calix[4]pyrrole ligand and the prepared organometallic compound as receptors for tetraalkylammonium chloride salts in dichloromethane and acetone. We describe the results of 1 H NMR, UV–Vis titrations and isothermal titration calorimetry (ITC) experiments in dichloromethane and acetone, aiming to thermodynamically characterize the formed complexes. The obtained results indicate a noticeable decrease in the binding affinity of the chloride for the mono‐gold(I) receptor 1 compared to the parent ligand 2 . The increase in the negative value of the electrostatic surface potential at the center of the aromatic ring of the gold(I) meso ‐aryl‐ethynyl substituent serves to explain the observed results and the presence in solution of the chloride complex of 1 as a mixture of two conformers. Abstract : Building a "two‐wall" calix[4]pyrrole : The synthesis and binding studies of an unprecedented organometallic "two‐wall" calix[4]pyrrole bearing one gold(I) phosphine residue at the upper rim is reported. The increase in the negative value of the electrostatic surface potential (ESP) at the center of the substituted aromatic wall produces stronger repulsive chloride‐π interactions in the resulting complexes compared to the parent ligand.